Buddhism and Moral Development in Family: พระพุทธศาสนากับการพัฒนาจริยธรรมครอบครัว - สังเมฆ, จิระศักดิ์ (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
Thai social culture is the way of living of people related to the teaching of Buddhism in many ways. The principles of Buddhism support the developments in many aspects of human living.These principles may be conflict with capitalism supporting productivity for demand of consume of people to stimulus economic system leading to damage of natural resource everlasting. Morality for selecting a couple which make the couple well matched. Morality for supporting husband and wife which make them in a sincere practice. Morality for supporting a son and a daughter which makes them to respect their parents. Morality for supporting parents which makes them into a suitable practice for their children. Morality for supporting the development economic system of country which makes it into a sustainable way. Morality for supporting economic potentiality of personal resource in their family which makes their asset to be stable and strong.